PENGEMBANGAN E-MODUL BERBASIS CANVA PADA TEMA DAERAH TEMPAT TINGGALKU SUBTEMA 1 PEMBELAJARAN 3 KELAS IV - Eka Sari Dewi; Yuyun Elizabeth; Fitri Anjaswuri (STKIP Subang, 2023)
This study aims to produce an e-module based on Canva on the theme of the area where I live, sub-theme 1 learning 3 in class IV SDN Cipayung 02 Depok city with a total of 29 students as respondents. This development uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research was conducted by analyzing needs, designing e-modules, then developing e-modules, after that validating the experts, and revising the product, then conducting a limited trial of Canva-based e-modules to selected respondents. The validation results provided by linguists with a percentage of 100% material experts with a percentage of 92.85% and media experts with a percentage of 92.8% indicate that the Canva-based e-module is declared valid and feasible to use. In the limited test phase, 29 students gave a very good response to the Canva-based e-module used with a percentage of 85.68%. Thus, the Canva-based e-module product on the theme of the area where I live, which was developed in this study, is proven to be valid and feasible to use in the learning process.